Teacher efforts in enhancing religious behavior among secondary school students - Ramadhan, Nabil Auliya; Lisnawati, Santi; Sa'diyah, Maemunah; Sari, Nila Mayang; Binhayeekhonoh, Sahroh (ATTARBIYAH: Journal of Islamic Culture and Education, 2025)
Religious behavior shapes attitudes, values, and practices within educational environments. This study investigates the efforts of teachers to enhance the religious behavior of Mattayom students at Solihuddin School. The research aims to understand student religious behavior, teacher efforts to improve it, and the inhibiting and supporting factors involved. A qualitative approach with a case study method was used, employing observation, interviews, and documentation, and analyzed using triangulation techniques. This study found that most mattayom students at Solihuddin School demonstrate generally positive religious behavior, although differences remain in understanding and participation. Teachers play a key role through modeling, personal guidance, and active engagement strategies. The effectiveness of these efforts is influenced by inhibiting factors, such as low student motivation and unsupportive environments, as well as supporting factors, including strong school policies, parental involvement, and proactive teaching. These findings highlight the importance of an integrated and collaborative approach to fostering students' religious development.